EXPRESSIVE ACTS IN BARRACK OBAMA’S PRESIDENTIAL SPEECH IN UNIVERSITAS INDONESIA - YUWONO, DODHIK (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: speech, speech acts, expressive acts Human have their own ways to express their feelings. One of the mediumto express emotion is language. Expressing emotion through language also can be performed when a person has a speech. It can be analyzed through one of speech acts theories, that is expressive act theory. Expressive act is psychological state of the speaker. It can be statements of thanking, pardoning, apologizing, welcoming, praising, etc. The researcher conducted a research about expressive act in Barrack Obama’s presidential speech in Jakarta, November, 10th 2010. There are two problems to be solved, namely: (1) what expressive acts are found in Barrack Obama’s presidential speech, and (2) what the strategies are used by Barrack Obama in uttering expressive acts.This research used qualitative approach because the analysis is in the form of description rather than number. Then, the research was conducted through documentary analysis since the researcher analyzed Obama’s utterances in his transcript speech containing expressive acts. The result of the research shows that there are six types of expressive acts used by Obama in his speech, namely (1) thanking, (2) greeting, (3) happiness, (4) sadness, (5) condolence, and (6) wishes. There are also five strategies used by Obama in performing those acts. Those were literal direct act, non literal direct act, literal indirect act, literal direct act + non literal direct act, and literal direct act + non literal indirect act. After discussing all of the data, it is concluded that the type of expressive act used more often in this speech is happiness. Since, the emotion that madeObama happy with the situation of his come back to Indonesia as a President ofUSA, so that he showed his happiness repeatedly. Based on the result of the study, the writer wants to give suggestions for the next researchers who are interested in the same field to conduct a research about expressive act in daily conversations. Since, by conducting a research in daily conversations, we can extend the theory of expressive act because daily conversations contain more complex utterances than formal speech. Moreover, the researcher hopes that this thesis can help to give a little vision or as a reference about expressive act.